Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2021
DOI: 10.3390/jcm10040841
|View full text |Cite
|
Sign up to set email alerts
|

Potential of Photodynamic Therapy Based on Sugar-Conjugated Photosensitizers

Abstract: In 2015, the Japanese health insurance approved the use of a second-generation photodynamic therapy (PDT) using talaporfin sodium (TS); however, its cancer cell selectivity and antitumor effects of TS PDT are not comprehensive. The Warburg effect describes the elevated rate of glycolysis in cancer cells, despite the presence of sufficient oxygen. Because cancer cells absorb considerable amounts of glucose, they are visible using positron emission tomography (PET). We developed a third-generation PDT based on t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 102 publications
(47 reference statements)
0
16
0
Order By: Relevance
“…After internalization in cells, a single irradiation of micelles with a NIR laser led to their death. Nanoprobes, including sodium talaporphin and Ce6 conjugated with glucose, have been synthesized [ 79 ]. Since cancer cells uptake a significant amount of glucose (Warburg effect), they can be detected by positron emission tomography (PET), which indicates the prospects for their using in theranostics.…”
Section: Porphyrin Photosensitizers For Cancer Photodynamic Therapymentioning
confidence: 99%
See 1 more Smart Citation
“…After internalization in cells, a single irradiation of micelles with a NIR laser led to their death. Nanoprobes, including sodium talaporphin and Ce6 conjugated with glucose, have been synthesized [ 79 ]. Since cancer cells uptake a significant amount of glucose (Warburg effect), they can be detected by positron emission tomography (PET), which indicates the prospects for their using in theranostics.…”
Section: Porphyrin Photosensitizers For Cancer Photodynamic Therapymentioning
confidence: 99%
“…Since cancer cells uptake a significant amount of glucose (Warburg effect), they can be detected by positron emission tomography (PET), which indicates the prospects for their using in theranostics. Similar nanoprobes are used as radio- and fluorescent-labeled antibodies targeting cancer cells in surgery for imaging and resection of tumor lesions [ 79 , 80 ].…”
Section: Porphyrin Photosensitizers For Cancer Photodynamic Therapymentioning
confidence: 99%
“…Next, PDT is known to cause acute inflammation, leading to immune stimulation and increasing the presentation of tumor-derived antigens to T-cells [28]. PDT using third-generation PS of glucose-conjugated chlorin demonstrated a stronger antitumor effect and induced immunogenic cell death compared with talaporfin sodium in a preclinical study [29]. Several immune checkpoint inhibitors have shown more favorable survival outcomes for esophageal cancer patients compared with conventional systemic chemotherapy in phase-III trials, and these have been introduced into the clinical practice for advanced esophageal cancer patients in recent years [30,31].…”
Section: Future Perspective and Conclusionmentioning
confidence: 99%
“…It has been shown that scavenger receptor MARCO antibodies can stop TAM-mediated immunosuppression and serves cancer immunotherapy [198]. According to the literature review, most of the novel TAM-based therapies usually rely on the natural characteristics of tumor or cancer cells, the immune system, and the tumor microenvironment [199]. However, the different TAM subpopulations, and the various recruitment and evolution process, which is raised from their regional differences, justifies the necessity of multi-targeted approaches for the implementation to fight against cancer [200].…”
Section: Modification In Transcription Factorsmentioning
confidence: 99%